Vulvar melanoma: A diagnostic challenge for young women - a case report. (September 2022) - Omari, Mouhsine; Zaimi, Adil; Kacem, Hanane Hadj; Afqir, Said
Abstract: Vulvar melanoma is a rare malignant tumor of the female genital sphere, representing postmenopausal women's prerogative, the diagnosis is based on immunohistochemicals analysis, and treatment requires a multidisciplinary approach. On account of its high metastatic potential as well as the late diagnosis given that it has non-specific clinical signs, the prognosis remains poor. In this study, we report the case of a woman of childbearing who presented a vaginal mass associated to chronic pelvic pain. Paraclinical investigations revealed a right vulvar tumoral process with pathological-looking inguinal adenomegalies on the right side with a necrotic center measuring 16.7 mm on the short axis, micronodules and secondary pulmonary nodules. The patient has been put under palliative chemotherapy, then passed out 8 months later. By this work, we attempt to review the diagnostic circumstances to better understand this delay, also to encourage self-examination and self-screening of abnormal lesions, as well as leveling the awareness of health professionals on this rare disease. Highlights: The vulvar melanoma is a rare and aggressive entity of the female's genital tract. The clinical signs remain non-specific; the diagnosis is based on immunohistochemical study. The prevention of vulvar melanoma requires awareness of health professionals on this rare disease, as well as patient education on self-examination of the genital tract and self-screening all atypical pigmentary lesions. The prognosis is very poor due to the delay in diagnosis and the high metastatic potential.